Knowledge Management in Planning and Control at Rolls-Royce - Clarke, Timothy David (2015)
Rolls-Royce (R-R) currently has no formal knowledge management processes in place within its planning and control function and relies on the knowledge of individual Superusers to answer knowledge-intensive queries from end users. This dissertation intends to investigate the formal methods of knowledge management that may be used to organise the knowledge required within planning and control in R-R. While R-R has existing policies relating to knowledge management, they relate mainly to management of the company’s intellectual property relating to the design of aircraft engines. While the knowledge used within the planning and control function does not directly relate to the company’s products it is key to the efficient and complaint operation of the organisation. As R-R is primarily involved in aerospace, there are also significant regulatory and legal obligations on all functions within the organisation to ensure the safety of the company’s engines. Combined with a large and complex SAP planning system implementation, there is significant opportunity for improved knowledge management in this area.